2007
DOI: 10.4049/jimmunol.178.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Granulysin-Mediated Tumor Rejection in Transgenic Mice

Abstract: Granulysin (GNLY) is a cytolytic molecule expressed by human CTL and NK cells with activity against a variety of tumors and microbes, including Mycobacterium tuberculosis. Although the molecular mechanism of GNLY-induced apoptosis of Jurkat T cells is well defined in vitro, no direct evidence for its in vivo effects has been demonstrated. Because there is no murine homologue of GNLY, we generated mice expressing GNLY using a bacterial artificial chromosome containing the human GNLY gene and its 5′ and 3′ flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 65 publications
1
68
0
Order By: Relevance
“…To confirm the role of PFN and GNLY in killer cell-mediated elimination of intracellular parasites, we assessed the killing of anti-CD3-coated T. cruzi-infected RAW 264.7 cells (a mouse macrophage cell line) by interleukin (IL)-15-cultured splenocytes from T. cruziinfected wild-type (WT), GNLY-transgenic (GNLY +/− ) 11 , PFN-deficient (Prf1 −/− ) and Prf1 −/− GNLY +/− mice ( Fig. 1d and Supplementary Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the role of PFN and GNLY in killer cell-mediated elimination of intracellular parasites, we assessed the killing of anti-CD3-coated T. cruzi-infected RAW 264.7 cells (a mouse macrophage cell line) by interleukin (IL)-15-cultured splenocytes from T. cruziinfected wild-type (WT), GNLY-transgenic (GNLY +/− ) 11 , PFN-deficient (Prf1 −/− ) and Prf1 −/− GNLY +/− mice ( Fig. 1d and Supplementary Fig.…”
mentioning
confidence: 99%
“…3b). Transgenic GNLY +/− mice were generated using a large Killer lymphocytes use granulysin, perforin and granzymes to kill intracellular parasites bacterial artificial chromosome that contains the 5 and 3 regulatory domains of the GNLY gene 11,15 . As a consequence, these mice express GNLY protein at levels similar to those in humans, but only in NK cells and CTLs.…”
mentioning
confidence: 99%
“…Granulysin homologs are found in humans, cows, pigs, and horses, but not in mice or rats (21,22). To test the physiologic role of granulysin, we used a bacterial artificial chromosome to generate GNLY transgenic mice (23). These animals have normal development and phenotype, and their lymphocytes express granulysin in a manner similar to human T and NK cells.…”
mentioning
confidence: 99%
“…Studies examining the regulation of granulysin are limited compared with those of perforin and granzymes, in part due to the lack of a murine gene homolog (26). Our results demonstrated that IL-2 stimulated and enhanced the expression of granulysin via transcription factor binding sites upstream of the granulysin promoter.…”
Section: Discussionmentioning
confidence: 54%
“…The upstream element (219,802 to 21,181 bp) of the human granulysin promoter was digested from a 186-kb human bacterial artificial chromosome clone RP11-439L14 with BglII and BstBI sites (26). The initial reporter gene construct pGL3219,802/+62 was assembled by cloning the digested fragment into the promoterless pGL3 basic reporter vector (Promega, Madison, WI), in which the human granulysin promoter and translation initiation site (21,181/+62) had been fused to the firefly luciferase gene (24).…”
Section: Luciferase Reporter Constructionmentioning
confidence: 99%